2019
DOI: 10.1139/cjas-2018-0241
|View full text |Cite
|
Sign up to set email alerts
|

Development of an equation to estimate the enteric methane emissions from Holstein dairy cows in Canada

Abstract: The aim of this study was to use dietary factors, including the type of fats, and animal characteristics, to predict enteric methane (CH4) emissions from dairy cows under Canadian conditions. For this purpose, 193 individual observations from six different trials assessing the impact of dietary modification on enteric CH4 production were analyzed. Animal [milk yield (MY), milk fat content, milk protein content, days in milk, body weight (BW), and dry matter intake (DMI)] and dietary variables [organic matter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
2
0
0
Order By: Relevance
“…The positive association between CH 4 production and MY or ECM is the result of the dilution effect of an increase in DMI, as observed by the positive relationship between DMI and MY ( r = 0.94, p < 0.001) or DMI and ECM ( r = 0.91, p < 0.001). In the current study, MPY was associated with a decrease in CH 4 emissions, and this agrees with Velarde-Guillén et al [ 100 ]. This is likely related to a greater propionate production yielding more glucose, microbial protein, and mammary protein synthesis signaling.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The positive association between CH 4 production and MY or ECM is the result of the dilution effect of an increase in DMI, as observed by the positive relationship between DMI and MY ( r = 0.94, p < 0.001) or DMI and ECM ( r = 0.91, p < 0.001). In the current study, MPY was associated with a decrease in CH 4 emissions, and this agrees with Velarde-Guillén et al [ 100 ]. This is likely related to a greater propionate production yielding more glucose, microbial protein, and mammary protein synthesis signaling.…”
Section: Discussionsupporting
confidence: 93%
“…2 (6.0%). The [ 19 ] slope-only model showed an overprediction of CH 4 production in the current study with a significant mean bias as assessed according to St-Pierre [ 83 ] (−18.9 g/d, p = 0.002), and these findings are consistent to those reported by others [ 16 , 22 , 100 ]. In contrast to our results, Appuhamy et al [ 22 ] observed 5.7% Y m in North American lactating dairy cows.…”
Section: Discussionsupporting
confidence: 92%